The Effect of Capital Intensity and Leverage on Profitability in Mining Companies on the IDX in 2019-2021 - Nadhifah, Isyfa Fuhrotun; Pristanila Firliana, Birnika (Jurnal Rekognisi Akuntansi, 2023)
This study aims to determine the effect of capital intensity ang leverage on company profitability. Independent variables used in this research are capital intensity and leverage. While variables dependent in this study is profitability. Research conducted on mining companies listed on the Indonesia Stock Exchange (IDX) with a sample of 25 companies obtained by purposive sampling method. The research results show that capital intensity and leverage do not have significant influence on profitability in mining companies in 2019-2021.